The impact of cytochrome 450 and Paraoxonase polymorphisms on clopidogrel resistance and major adverse cardiac events in coronary heart disease patients after percutaneous coronary intervention - Zhaowei Zhang; Mingxiao Chen; Long Zhang; Qiang Zhao (BMC, 2020)
Abstract Background Clopidogrel is an inactive prodrug, it catalyzed into its active form by Cytochrome 450 and Paraoxonase-1(PON-1). polymorphisms of genes encoding these enzymes will affect the efficacy of Clopidogrel. The main objective of our study was to investigate the association of CYP2C19*2, CYP2C19*3 and PON-1Q192R polymorphisms with Clopidogrel resistance and major adverse cardiac events in Jin Hua district in the middle of Zhe Jiang Province in China. Methods One hundred sixty coronary heart disease patients with percutaneous coronary intervention, who were followed-up for 1 year, were enrolled in our study. These patients were co-administered aspirin 100 mg/d and clopidogrel 75 mg/d following a loading dose of 300 mg. The ADP-induced platelet aggregation rate was measured by Platelet aggregator. Genotypes of CYP2C19*2, CYP2C19*3, PON-1Q192R were determined using Sanger sequencing in all patients. Various clinical data were collected. Results The frequencies of CYP2C19*2, CYP2C19*3 and PON-1Q192R homozygous mutant genotypes were significantly lower in non-responders than those in responders. After for all variables, CYP2C19*2, CYP2C19*3 and PON-1Q192R independently increased the risk of clopidogrel resistance with adjusted ORs 46.65(95% CI,1.77-25.04; p = 0.005); 22.74(95% CI, 3.11-166.27; p = 0.002); 5.69 (95% CI,1.06-30.47; p = 0.042). Over a follow-up of 12 months, the incidence of major adverse cardiac events (MACE) in CYP2C19*1/*2, *1/*3, *2/*2, *2/*3 was significantly higher than no mutant genotype (18/40vs.2/63,3/9vs.2/63, 11/6vs.2/63, 7/1vs2/63, respectively). There was no significant correlation between PON-1Q192R mutant allele and MACE. Conclusion Our study was first time to report on CYP2C19 and PON-1 polymorphisms in Jin Hua population in the middle of Zhe Jiang province in China. The carriage of CYP2C19*2 or *3 mutant allele significantly reduced the platelet response to clopidogrel and increase the MACE. The carriage of PON-1 mutant allele also significantly reduced the platelet response to clopidogrel, but would not increase the major adverse cardiac events after 1 year follow-up. Trial registration ChiCTR, ChiCTR1800018316. Registered 11 September 2018 - prospective registered, http://www.chictr.org.cn/edit.aspx?pid=30927&htm=4.